2003
DOI: 10.1016/s0014-5793(03)01221-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the processivity of endopolygalacturonase I from Aspergillus niger

Abstract: Endopolygalacturonase I is a processive enzyme, while the 60% sequence identical endopolygalacturonase II is not. The 1.70 A î resolution crystal structure of endopolygalacturonase I reveals a narrowed substrate binding cleft. In addition, Arg96, a residue in this cleft previously shown to be critical for processivity, interacts with the substrate mimics glycerol and sulfate in several well-de¢ned conformations in the six molecules in the asymmetric unit. From this we conclude that both Arg96 and the narrowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 36 publications
8
61
0
4
Order By: Relevance
“…These reports highlight the essential role of GH28 proteins in pectin degradation and developmentally regulated cell separation in plants. GH28 proteins have been extensively characterized structurally for their catalytic mechanisms, reaction processivity and exo/endo selectivity (Armand et al, 2000;Pages et al, 2000;Shimizu et al, 2002;van Pouderoyen et al, 2003). Our modeling study indicated that RCPG shares a conserved protein folding with known GH28 endo-PGs, as well as perfectly conserved positioning of amino acid residues that are known to be important for catalysis and substrate recognition.…”
Section: Brn1 Directly Controls a Gene That Encodes A Cell Wall Modifmentioning
confidence: 66%
See 1 more Smart Citation
“…These reports highlight the essential role of GH28 proteins in pectin degradation and developmentally regulated cell separation in plants. GH28 proteins have been extensively characterized structurally for their catalytic mechanisms, reaction processivity and exo/endo selectivity (Armand et al, 2000;Pages et al, 2000;Shimizu et al, 2002;van Pouderoyen et al, 2003). Our modeling study indicated that RCPG shares a conserved protein folding with known GH28 endo-PGs, as well as perfectly conserved positioning of amino acid residues that are known to be important for catalysis and substrate recognition.…”
Section: Brn1 Directly Controls a Gene That Encodes A Cell Wall Modifmentioning
confidence: 66%
“…GH28 proteins have been extensively studied in bacteria and fungi, and their catalytic mechanism and reaction selectivity between endo-and exo-PG have been elucidated at the atomic level (Abbott and Boraston, 2007;Shimizu et al, 2002;van Pouderoyen et al, 2003). Our modeling analyses indicate that RCPG folds into a β-helical structure with an open-ended substrate-binding cleft typical of endo-PGs (Fig.…”
Section: Rcpg Promotes Cell Separationmentioning
confidence: 81%
“…The multiple attack action is often referred to by the more generic term "processivity" (Breyer & Matthews 2001). Many enzymes that synthesise, modify or degrade polymers, such as granule bound starch synthase I (Denyer et al 1999), DNA polymerase (Kelman et al 1998), and endopolygalacturonase I from Aspergillus niger (van Pouderoyen et al 2003), act by a processive action pattern.…”
Section: Definitionsmentioning
confidence: 99%
“…The specialized activity of this enzyme was described to be due to inserted stretches of amino acid residues that transform the active site from the open-ended channel observed in randomly cleaving PGs (Pickersgill et al 1998;van Santen et al 1999;Cho et al 2001;Federici et al 2001;Shimizu et al 2002;van Pouderoyen et al 2003) to a closed pocked-like active centre that restricts the enzyme to the exclusive attack of non-reducing end of substrate. Similar arrangement of the active site can be supposed for exoPGs, too, but with the catalytic site situated between the first and the second subsite instead of the second and the third one.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional structures of several PGs have been reported (Pickersgill et al 1998;van Santen et al 1999;Cho et al 2001;Federici et al 2001;Shimizu et al 2002;van Pouderoyen et al 2003) but only one structure of exopolygalacturonosidase (from Yersinia enterocolitica) with an accompanying explanation of the molecular determinants for its specialized activity (Abbott & Boraston 2007). Tertiary structure of exoPG or generally of any plant pectate hydrolase has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%